Tathawwur al-Mar’ah al-Muslimah fi al-Mujtama’ al-Libyi - Masoud, Amera J; Syafaq, Hammis (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2022)
Abstract: This article discusses the development of Muslim women in Libya. Women in society play a role that surpasses the role of men in the growth and development of society, as women are half of society. Women in the pre-Islamic era were a commodity that men owned, and they did not have any rights. At the beginning of Islam's advent, women's status changed a lot, and women became entitled to many rights and status. In addition to obtaining all their rights recognized by the Islamic religion and accompanied by Libyan legislation, Libyan women have incited the inclusion of women's rights through the ratification of international conventions and women's participation in all fields. Women's rights are their right to education, their right to choose a husband, their right to litigation, to defend their financial rights and to remedy injustice against them, women's right to work and to hold public office, women's right to judicial and litigation functions, women's right to political participation and community development, and women's right to health care. Keywords: Women, Muslimah, Islam, Libya. الملخص: إن هذه المقالة تبحث تطور المرأة المسلمة في ليبيا. المرأة في المجتمع تلعب دورًا يتفوق على دور الرجل في نماء المجتمع وتطوره، فالمرأة هي نصف المجتمع. كانت المرأة في الجاهلية عبارة عن سلعة تخضع لملكية الرجل ، ولم تكن لها أي من الحقوق. وبداية ظهور الاسلام تغير وضع المرأة كثيرا واصبحت المرأة لها كثيرا من الحقوق واصبحت لها مكانة. إن المرأة الليبية اضافة الي حصولها على جميع حقوقها التي اقرها الدين الاسلامي وواكبتها التشريعات الليبية التطور فحرضت على تضمين حقوق المرأة من خلال التصديق على المواثيق الدولية ومشاركة المرأة في كل المجالات. فحقوق المرأة هي حقّها في التربية والتعليم، حقّها في اختيار الزوج وحقها في التَّقاضي والدِّفاع عن حُقوقها الماليّة ورفع الظلم عنها، حق المرأة في العمل و تولي الوظائف العامة، حق المرأة في تولي الوظائف القضائية والتقاضي، حق المرأة في المشاركة السياسية و تنمية المجتمع، وحق المرأة والرعاية الصحية. الكلمات الرئيسيه: المرأة، المسلمة، اسلام، ليبيا.